The Role of Financial Technology and Intellectual Capital in Mediating the Influence of Financial Literacy on Business Sustainability - Alni Rahmawati; Micola Imanda Julian (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to test the influence of financial literacy on business sustainability with Intellectual capital and Financial technology as mediators in MSMEs in the Special Region of Yogyakarta. This study uses a quantitative approach, the type of data is primary data. The subjects in this study are actors, managers, actors as well as managers of MSMEs. The sampling technique used is purposive sampling. Data was collected through questionnaires, the sample number was 100 respondents. The analysis tool using the analysis path is supported by Smart PLS 4.0 software. The results of the study include financial literacy has a significant positive effect on business sustainability, financial literacy has a significant positive effect on intellectual capital, financial literacy has a significant positive effect on financial technology, intellectual capital has a significant positive effect on business sustainability, financial technology has a significant positive effect on business sustainability, intellectual capital mediates the influence of financial literacy For business sustainability, financial technology mediates the influence of financial literacy on business sustainability. The implication of this research is that financial management is an important component in making effective decisions and can improve business sustainability.